Influence of experimental parameters on in vitro human skin permeation of Bisphenol A - Reale, E.; Berthet, A.; Wild, P.; Vernez, D.; Hopf, N.B. (Toxicology in vitro, 2021)
Bisphenol A (BPA) in vitro skin permeation studies have shown inconsistent results, which could be due to experimental conditions. We studied the impact of in vitro parameters on BPA skin permeation using flow-through diffusion cells with ex-vivo human skin (12 donors, 3–12 replicates). We varied skin status (viable or frozen skin) and thickness (200, 400, 800 μm), BPA concentrations (18, 250 mg/l) and vehicle volumes (10, 100 and 1000 μl/cm2). These conditions led to a wide range of BPA absorption (2%–24% after 24 h exposure), peak permeation rates (J = 0.02–1.31 μg/cm2/h), and permeability coefficients (Kp = 1.6–5.2 × 10−3 cm/h). This is the first time steady state conditions were reached for BPA aqueous solutions in vitro (1000 μl/cm2 applied at concentration 250 mg/l). A reduction of the skin thickness from 800 and 400 μm to 200 μm led to a 3-fold increase of J (P < 0.05). A reduction of the vehicle volume from 1000 to 100 led to a 2-fold decrease in J (P > 0.05). Previously frozen skin led to a 3-fold increase in J compared to viable skin (P < 0.001). We found that results from published studies were consistent when adjusting J according to experimental parameters. We propose appropriate J values for different exposure scenarios to calculate BPA internal exposures for use in risk assessment. •Steady-state conditions were reached with a saturated BPA solution at 1 ml/cm2.•BPA Kp increased from 1.6 to 5.2 × 10−3 cm/h with decreasing skin thickness.•Worst-case scenario: J = 1.3 μg/cm2/h and Kp = 5.2 × 10−3 cm/h for 200 μm thick skin.•Different experimental conditions explain inconsistencies in published BPA results.